Early maternal Zika infection predicts severe neonatal neurological damage: results from the prospective Natural History of Zika Virus Infection in Gestation cohort study. (8th October 2020) - Coutinho, CM; Negrini, SFBM; Araujo, DCA; Teixeira, SR; Amaral, FR; Moro, MCR; Fernandes, JDCP; da Motta, MSF; Negrini, BVM; Caldas, CACT; Anastasio, ART; Furtado, JM; et al.
Abstract : Objective: To define the prevalence of adverse outcomes of maternal infection in a large cohort of ZIKV‐infected Brazilian women and their infants. Design: Prospective population‐based cohort study. Setting: Ribeirão Preto's region's private and public health facilities. Population: Symptomatic ZIKV‐infected mothers and their infants. Methods: Prenatal/early neonatal data were obtained for all mother–child pairs. A subgroup of infants had cranial ultrasonography, eye fundoscopy, hearing and neurological examinations and Bayley III screening tests within 3 months of age. Main outcome measures: Prevalence of pregnancy losses and anomalies detected at birth or within 3 months according to the gestational age of infection. Results: Overall, 511 ZIKV‐infected women were identified from a total of 1116 symptomatic women; as there were two twins, there were a total of 513 fetuses included. Of these, 13 (2.5%; 95% CI 1.5–4.3) presented with major signs of congenital Zika syndrome (CZS). Of the 511 women, there were 489 livebirths and 24 (4.7%) pregnancy losses (20 miscarriages and four stillbirths). ZIKV‐related anomalies occurred in the offspring of 42/511 (8.2%) mothers. Microcephaly or other CNS malformations were diagnosed in 1/4 (25.0%) stillbirths and in 19/489 (3.9%; 95% CI 2.5–5.9) of the liveborn infants. Fetal abnormalities were 14.0 (95% CI 7.6–26.0) times more likely with gestational infection occurring in ≤11 weeks. On follow up of 280 asymptomatic infants, 2/155 (1.3%) had eye abnormalities, 1/207 (0.5%) had CNS imaging findings and 16/199 (8%) presented neurological alert signs. Conclusions: This prospective population‐based study represents the largest Brazilian cohort study of ZIKV in pregnancy. Congenital anomalies potentially associated with CZS are less frequent than previously thought. There is a strong association between the gestational age of infection (≤11 weeks) and a poorer early infant prognosis. A notable proportion of apparently asymptomatic newborns can present with subclinical findings within 3 months of age. Tweetable abstract: ZIKV and pregnancy: adverse outcomes are less common, more prevalent for first‐trimester infections, and potentially subclinical. Tweetable abstract: ZIKV and pregnancy: adverse outcomes are less common, more prevalent for first‐trimester infections, and potentially subclinical.